Linking selected variables with direct and indirect effect on young swimmer's performance - Morais, J.E. (2018)
One of the main goals of swimming research is to identify the scientific domains and/or variables that predict swimming performance in children (i.e., young athletes) in the perspective of detecting future talents (1). Nevertheless, research in young athletes should be less invasive, expensive and timeconsuming than in adult/elite counterparts (2). In this sense, several authors (2-4) on regular basis estimate and/or measure variables in different scientific domains (i.e., anthropometric, hydrodynamic, kinematical and energetic) that are easy to collect and might predict performance and/or detect talented swimmers.